PENGARUH ACUPRESSURE TERHADAP KENAIKAN BERAT BADAN BALITA USIA 13-36 BULAN - Suryani, Lilis; Retno Wati, Dwi (PRIMA WIYATA HEALTH, 2023)
The condition of having difficulty eating is one of the problems that has an impact on the lack of nutritional intake in toddlers. Eating disorders in children must be treated immediately because they can have an impact on malnutrition. One effort to increase body weight is by acupressure, which is an action that is emphasized at certain points that can stimulate appetite in toddlers so that they can increase body weight. The purpose of this study was to determine the effect of acupressure on weight gain in toddlers aged 13-36 months. This type of research is a quasy experiment with a pretest-posttest control group design. The sample for this study was 60 toddlers who met the criteria, taken by random sampling technique. The independent variable is acupressure, while the dependent variable is toddler's weight. The instruments used were observation sheets, checklists, baby oil and scales. The method of data collection was by measuring the toddler's weight before and after the acupressure treatment 4 times for 4 weeks. Data analysis using Independent Sample T-Test. The results of this study after acupressure was carried out on 30 toddlers in the intervention group, there was an average increase in toddler's weight by 335 grams (p value = 0.000). The conclusion from the results of this study is that acupressure affects toddlers' weight gain. Therefore Acupressure is suggested to be used as a non-pharmacological therapy to increase appetite so that it can increase the weight of toddlers